Inquiry skills for biology teacher candidates in plant anatomy practicum - Setiono; Nuryani Y Rustaman; Adi Rahmat; Sri Anggraeni (Universitas Ahmad Dahlan, 2021)
Inquiry skills are important basic skills that science teachers must possess. Inquiry skills underlie the standard implementation of the science learning process. This descriptive study aims to obtain an overview of the mastery of inquiry skills possessed by prospective biology teacher students in plant anatomy practicum. The research method used in this research is descriptive method. The research subjects in this study were prospective biology teacher students (n=42). The instruments used in this research are inquiry skills tests and interviews. The results showed that the average student inquiry skills was 43.36. This result is still below the indicator of completeness in mastering skills, which is 75. The acquisition of an inquiry skills score on the indicators of identifying problems (29.76), designing experiments and carrying out experiments (50.79), analyzing and interpreting data (54.76), constructing explanations (42.86), generate arguments from a number of evidences (43.33) and communicate information (38.69). The conclusion of this study is that the verification practicum learning experience that has been experienced by students has not been able to develop student inquiry skills optimally, so it is necessary to design lecture programs both in class and in laboratory to develop students' inquiry skills.